?-Lipoic Acid Has the Potential to Normalize Copper Metabolism, Which Is Dysregulated in Alzheimer's Disease. - Metsla, K.; Kirss, S.; Laks, K.; Sildnik, G.; Palgi, M.; Palumaa, T.; Tõugu, V.; Palumaa, P. (Journal of Alzheimer's disease : JAD, 2022)
Alzheimer's disease (AD) is an age-dependent progressive neurodegenerative disorder and the most common cause of dementia. The treatment and prevention of AD present immense yet unmet needs. One of the hallmarks of AD is the formation of extracellular amyloid plaques in the brain, composed of amyloid-? (A?) peptides. Besides major amyloid-targeting approach there is the necessity to focus also on alternative therapeutic strategies. One factor contributing to the development of AD is dysregulated copper metabolism, reflected in the intracellular copper deficit and excess of extracellular copper. In the current study, we follow the widely accepted hypothesis that the normalization of copper metabolism leads to the prevention or slowing of the disease and search for new copper-regulating ligands. We used cell culture, ICP MS, and Drosophila melanogaster models of AD. We demonstrate that the natural intracellular copper chelator, ?-lipoic acid (LA) translocates copper from extracellular to intracellular space in an SH-SY5Y-based neuronal cell model and is thus suitable to alleviate the intracellular copper deficit characteristic of AD neurons. Furthermore, we show that supplementation with LA protects the Drosophila melanogaster models of AD from developing AD phenotype by improving locomotor activity of fruit fly with overexpression of human A? with Iowa mutation in the fly brain. In addition, LA slightly weakens copper-induced smooth eye phenotype when amyloid-? protein precursor (A?PP) and beta-site A?PP cleaving enzyme 1 (BACE1) are overexpressed in eye photoreceptor cells. Collectively, these results provide evidence that LA has the potential to normalize copper metabolism in AD.